Life and death: social perspectives on biblical bodies - Stavrakopoulou, Francesca (The Hebrew Bible in social perspective, 2021)
"This book explores some of the social, material, and ideological dynamics shaping life and death in both the Hebrew Bible and ancient Israel and Judah"--